KONSTRUKSI BUDAYA MASYARAKAT JAWA : STUDI TERHADAP NILAI BUDAYA KEMISKINAN MASYARAKAT MUSLIM MALANG JAWA TIMUR - Purwadi, Agus; El-Rumi, Umiarso (JURNAL ISLAM NUSANTARA, 2020)
This article focuses on constructing a culture of poverty that is motivated by religious attitudes in Malang, East Java. They consider poverty to be given human reality, and its existence cannot be shifted and changed. Based on this focus, this research takes a qualitative research approach with the type of phenomenology. This research uses Loren Demerath's Knowledge-Based Affect Theory as a perspective. Meanwhile, to analyze the research data using interactive analysis by Miles and Hubermann. This research finds that the views, attitudes, and actions of the poor emerge and imbued with Javanese expressions and are associated with religious doctrine interpretation. They consider mental fatalistic (nrimo ing pandum) to be the same as religious values such as patience and sincerity so that poverty is considered the destiny of God. This mentality position as legitimacy for their poverty. Even their views inspire the orientation of economic behavior, which they wrap with a spiritual dimension. The primary purpose of their life does not lie in material attainment but lies in the harmonization of life in societyÂ